IMPROVING THE ACCOUNTING AND VALUATION OF BIOLOGICAL ASSETS: THEORETICAL, METHODOLOGICAL AND REGULATORY APPROACHES (E Global Congress, 2026)
This article comprehensively analyzes the theoretical foundations, methodological, and regulatory aspects of accounting and valuation of biological assets. Modern approaches to accounting for biological assets are studied based on international practices, particularly the requirements of International Accounting Standard IAS 41 “Agriculture.” The research findings demonstrate that the fair value approach plays a dominant role in the valuation of biological assets, and scientific-practical recommendations aimed at improving the accounting system have been developed.